Design thinking - Clarke, Rachel Ivy (ALA Neal-Schuman, 2020)
"The Library Futures Series continues with this primer on design thinking, broadly defined as an approach to problem solving which prioritizes empathy with and deeper understandings of users to define a problem; actively engages in prototyping to develop solutions; and iterates solutions through implementation and resulting modification. Clarke, a researcher whose work has systematically examined the capacity of design thinking to revolutionize LIS education and the exploration of diverse library reading materials, guides readers through this trend. After introducing the concept, she outlines the steps of the design thinking process model. She then shares various examples of design projects in libraries, illustrating how design thinking extends beyond just space planning or website design and is applicable to all library products and services. She also demonstrates the ways in which design can either enable or stifle such foundational library values as intellectual freedom, diversity, and access. Concluding with a rousing call to action for all librarians to recognize their positions as designers, this book will encourage readers to recognize how design thinking can empower libraries."-- Provided by publisher.
Keywords: Library planning.; Library administration -- Decision making.; Problem solving.; Critical thinking.; Design -- Methodology.; Libraries -- Aims and objectives.; Problem Solving; Bibliothèques -- Planification.; Bibliothèques -- Administration -- Prise de décision.; Résolution de problème.; Pensée critique.; Design -- Méthodologie.; Bibliothèques -- Finalités.; Critical thinking; Design -- Methodology; Libraries -- Aims and objectives; Library administration -- Decision making; Library planning; Problem solving